ANALISA ZONA PRODUKTIF PADA SUMUR X-004 BERDASARKAN DATA WELL LOGGING DAN KORELASI SUMUR SEKITARNYA - Sri Nugroho, Lastio
The Hydrocarbon searching process will lead us to perforation process. The determination of perforation point can be done based on well logging analysis and should be done in productive zones. From the result of well logging, the analysis consist of rock lithology, volume shale, porosity, resistivity and water saturation. Those data wil be processed furthermore which lead to accurate data. The objective of this paper is to determine productive zones in well X-004. In this paper, this study using data from well X-004, with the depth interval is between 1250 m to 1450 m. Well X-004, revealed to be an oil well, is using open-hole completion. Log data which will be analyzed in this study consist of Gamma Ray Log, Resistivity Log, dan Porosity Log, either Sonic Log, Neutron Log or Density Log as well. The execution begins on calculation of vshale, and then calculation of porosity, determination of Rw, Sw calculation and in the end determination the productive zones based on all those data. From this paper, we can obtain 4 potential zones which are qualified based on data calculation.